PENGARUH STRUKTUR AKTIVA DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL - Hermaya Ompusunggu (LPPM Universitas Putera Batam, 2020)
The purpose of this research is to exemine the effect of asset structure and sales growth to the capital structure. The data in this research is the secondary data by using financial statement data. The population in this research were companies which are listed in the Indonesia Stock Exchange with the mining sector from 2014 to 2018. The sample collection technique has been done by using purposive sampling and 8 (eight) companies which meet the criteria have been selected as the research samples. The measurement of capital structure has been done by Debt to Equity Ratio (DER). The analysis has been done by using multiple linear regression. The result of the research shows the partial regression analysis is asset structure significant effect on capital structure with significance 0,317 > 0,05 and sales growth significant effect on capital structure with significance 0,039 < 0,05. While the results obtained simultaneously variable asset structure and sales growth significantly influence capital structure with significance 0,039 < 0,05.